2016
DOI: 10.1103/physrevc.93.045201
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the COSY dibaryon candidate tonpelastic scattering measurements

Abstract: The case for a dibaryon resonance, appearing in np scattering, has support from a WASA-at-COSY measurement of the polarization quantity Ay over a center-of-mass energy region suggested by structures seen earlier in two-pion production experiments. Here we compare fits with and without an associated pole in order to clarify the impact of these COSY data. We then consider what further np scattering measurements would most clearly distinguish between the pole and nonpole fit results.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…results for the analyzing power, indeed, revealed a pole in the coupled 3 D 3 − 3 G 3 partial waves at the position (2380 ± 10) − i(40 ± 5) MeV -fully consistent with the findings in the two-pion production reactions [32][33][34]. The Argand plot of the resonating 3 D 3 partial wave is shown in Fig.…”
Section: * (2380) -A Genuine Dibaryon Resonancesupporting
confidence: 75%
See 1 more Smart Citation
“…results for the analyzing power, indeed, revealed a pole in the coupled 3 D 3 − 3 G 3 partial waves at the position (2380 ± 10) − i(40 ± 5) MeV -fully consistent with the findings in the two-pion production reactions [32][33][34]. The Argand plot of the resonating 3 D 3 partial wave is shown in Fig.…”
Section: * (2380) -A Genuine Dibaryon Resonancesupporting
confidence: 75%
“…For the sensitivity of other observables to the d * resonance contribution see Ref. [32] Since there were no analyzing power data in the region of interest, corresponding analyzing power measurements extending over practically the full angular range were carried out with WASA at COSY -again in the quasi-free mode, but in inverse kinematics by use of a polarized deuteron beam hitting the hydrogen pellet target [33,34].…”
Section: * (2380) -A Genuine Dibaryon Resonancementioning
confidence: 99%
“…We do not deal here with the model of Gardestig, Fäldt and Wilkin [57], since this has been designed specifically for the ABC effect in the double-pionic fusion to 4 He and is not applicable to the basic double-pionic fusion to the deuteron.…”
Section: Description Of the D * (2380) Resonance Processmentioning
confidence: 99%
“…Recently it was shown that there is a resonance pole at (2380±10)−i(40±5) MeV in the 3 D 3 − 3 G 3 coupled partial waves based on a SAID partial-wave analysis, which included new data from COSY on the analyzing power of np scattering [1][2][3][4]. This finding matches perfectly with the I(J P ) = 0(3 + ) resonance structure observed at √ s ≈ 2.37 GeV with a width of 70 MeV in the total cross section of the double-pionic fusion reactions pn → dπ 0 π 0 and pn → dπ + π − [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The relative phases between the 3 D 3 and 3 G 3 partial waves are determined to be ∼ 4 • from the AD14 SAID partial wave analysis [10,38]. Using |d * ( 3 D 3 )| 2 |d * ( 3 G 3 )| 2 = 9 from the same analysis we can simplify the expression:…”
Section: Resultsmentioning
confidence: 99%